A concessão ex offício da tutela antecipada no contexto da efetividade processual - Figuerôa, Bruno Angelim (2008)
This scientific paper examined the possibility of the magistrate to grant, in a discretionary way, the anticipatory technique disciplined in Article 273 of the Brazilian Civil Procedural Code, because of the effectiveness of the procedural context. To accomplish that, the jurisdictional guardianship was analyzed under the fundamental rights perspective, focusing on time and process, the phases of the evolution of the procedural theory, the need for a constitutional interpretation of the laws and the implications of the fundamental principals in the process. It was also necessary to understand, through the instrumental point of view, the judge s power-duty to safeguard and the incidence of the fungibility principal around urgent matters, defending the unified nature of the reassuring and satisfying techniques. And, therefore, the disconnection of the ordinarization and cognition ending, plus assessing this theme under compared law analyzes, especially in the countries that influenced the Brazilian law system. It was highlighted, in this subject, that formalism for the sake of formalism could not be accepted, as well as the procedural technicism as an obstacle to a sound analysis of each concrete situation and the very assurance of the best possible efficiency of the material guardianship obtained via procedural tool. The re-designing of the anticipated guardianship of the parental right could not be ignored, momentarily when one seeks to demonstrate the efforts that, for a long time, have been used to favor a faster and fairer judicial service. Some constraints, written by the ones who pay reverence to legality and a rigid concept of the procedural institutes, have been analyzed, those points are easily surpassed by the need for effectiveness of the legal guardianship. At the end, the research checked the incidence of the proportionality, reasonability and inter-subjective cooperation principals as main factors to the granting of the anticipatory urgency institute, without the necessary lawful formality (express petition by the one interested). Summing everything up, we search, hence, to legitimate the judge the one who interprets and is a creative operator of the legal system to interact with the others procedural subjects, thinking of the goods and interests on the line in each case, as to autonomously act in the process aiming the protection of material rights and the very utility of the final ruling. Only from this conception, the anticipatory guardianship institute will fulfill its true purpose which is to avoid improper time dilations in a process and assure justice in a timely manner